A Historical Review of African Scholarship and the Decolonial Discourse: Challenges and Prospects - Juliet Munyaradzi (The Thinker)
African scholarship plays an important role in asserting the value of African epistemologies and those of the global South in the knowledge economy. This is pertinent to higher education in postcolonial Africa, whose indigenous knowledge systems and intellectual legacies have played peripheral roles because of coloniality and the global neoliberal trends. This paper presents a historical review of a generation of African scholarship that spans from the last half of the twentieth century to date. It does so with the view of exploring the developments, challenges and prospects experienced by African scholars in their pursuit of African knowledges and the decolonisation discourse in the higher education sector. The first part of the paper provides a backdrop through an analysis of some selected major research on the nature of African scholarship published in the last half of the twentieth century, and its contributions to the decolonisation discourse on the continent. The second part examines the nature of contribution of African scholarship to knowledge production in the twenty-first century. That section critically analyses the challenges and opportunities which have been encountered in reshaping the discourses of knowledge production and decolonisation in theory and practice. It is concluded that in its distinctiveness in asserting African and marginalised knowledge systems as valid and relevant, and operating in spaces of struggle, the African scholarship should continue to contribute to the interrogation of the objectivity of Eurocentric, neoliberal thought. The paper recommends the promotion of African scholarship in shaping the decolonisation of knowledge production.